THE PRACTICE OF DAKWAH COMMUNICATION TOWARDS INDIGENOUS COMMUNITY IN SELANGOR - Abu Sofi bin Hasbullah; Suhailiza binti Md. Hamdani (IAI Al-Mawaddah Warrahmah Kolaka, 2022)
Penggerak Masyarakat Orang Asli (PMOA) plays an important role towards the Indigenous community including looking after the welfare and and also contributed to the development of da'wah. Therefore, this article aims to identify the communication da'wah used by preachers and the challenges of preaching towards Indigenous community. This qualitative study uses a case study design. The data were obtained through semi -structured interviews involving a total of Nine Penggerak Masyarakat Orang Asli (PMOA) in the State of Selangor as participants. The data were arranged and coded according to themes and categories resulting from the complete transcript. Data were also analyzed descriptively. The results of the study shows that the method most widely used by Penggerak towards Indigenous community is da'wah bil hal. Among them are visiting the homes of Indigenous community, carrying out activities with Indigenous community and others.